From the Schwarzschild Anti-de Sitter Black Hole to the Conformal Field Theory - Akram Sadat Sefiedgar (Advances in High Energy Physics)
The emergence of the quantum gravitational effects in a very high energy regime necessitates some corrections to the thermodynamics of black holes. In this letter, we investigate a possible modification to the thermodynamics of Schwarzschild anti-de Sitter (SAdS) black holes due to rainbow gravity model. Using the correspondence between a (d+1)-dimensional SAdS black hole and a conformal filed theory in d-dimensional spacetime, one may find the corrections to the Cardy-Verlinde formula from the modified thermodynamics of the black hole. Furthermore, we show that the corrected Cardy-Verlinde formula can also be derived by redefining the Virasoro operator and the central charge.